Ninth International Conference on Information Visualisation (IV'05)
DOI: 10.1109/iv.2005.32
|View full text |Cite
|
Sign up to set email alerts
|

Collision Problem: Characteristics for a Taxonomy

Abstract: The Collision problem appears within many fields. The specific characteristics that can be identified in different problems lead to the broad set of specialized algorithms that appear in the literature. This paper deals with the first step needed to address the Collision Problem Taxonomy challenge: a survey that compiles and suggests a set of characteristics that could be used to discriminate collision problems, i.e. to generate the taxonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…A significant challenge is the need to compute collisions and forces over very short time frames (60-1000 Hz) to support interactive manipulation of complex CAD models. Lin and Gottaschalk [17] and Jimenez et al [18] present a survey of 3D collision detection algorithms and Borro et al [19] organize these algorithms into a taxonomy. Voxel-based methods, such as Voxmap pointshell, have proven especially effective in simulating full 6DOF haptic interactions [20], but the reliance on using approximate geometry for collision detection presents a challenge when faced with assembly of low clearance parts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant challenge is the need to compute collisions and forces over very short time frames (60-1000 Hz) to support interactive manipulation of complex CAD models. Lin and Gottaschalk [17] and Jimenez et al [18] present a survey of 3D collision detection algorithms and Borro et al [19] organize these algorithms into a taxonomy. Voxel-based methods, such as Voxmap pointshell, have proven especially effective in simulating full 6DOF haptic interactions [20], but the reliance on using approximate geometry for collision detection presents a challenge when faced with assembly of low clearance parts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several algorithms that use polygonal data for collision detection were designed by researchers at the University of North Carolina and include I-collide [23], SWIFT [24], RAPID [25], V-collide [26], SWIFT++ [27], and CULLIDE [28].Other methods such as V-Clip [29] and VPS [30] have also been proposed to use in immersive VR applications. A comprehensive review of collision detection algorithms can be found in [31,32] and a taxonomy of collision detection approaches can be found in [33].…”
Section: Collision Detectionmentioning
confidence: 99%